Can gender- and nutrition-sensitive agricultural programs improve resilience? Medium-term impacts of an intervention in Bangladesh - Hoddinott, John F.; Ahmed, Akhter; Quisumbing, Agnes R.; Rakshit, Deboleena (International Food Policy Research Institute, 2023)
There are few studies that rigorously assess how agricultural and nutrition related interventions enhance resilience and even fewer that incorporate a gendered dimension in their analysis. Mindful of this, we address three knowledge gaps: (1) Whether agricultural interventions aimed at diversifying income sources and improving nutrition have sustainable impacts (on asset bases, consumption, gender-specific outcomes and women’s empowerment, and on diets) that persist after the intervention ends; (2) whether such interventions are protective when shocks occur? and (3) whether these interventions promote gender-sensitive resilience. We answer these questions using unique data, a four-year post-endline follow up survey of households from a cluster-randomized controlled trial of a nutrition-and-gender-sensitive agricultural intervention in Bangladesh. We find that treatment arms that included both agriculture and nutrition training had sustainable effects on real per capita consumption, women’s empowerment (as measured by the pro-WEAI), and asset holdings measured four years after the original intervention ended. Treatment arms that included both agriculture and nutrition training (with or without gender sensitization) reduced the likelihood that households undertook more severe forms of coping strategies and reduced the likelihood that household per capita consumption fell, in real terms, by more than five percent between in the four years following the end of the intervention. The treatment arm that only provided training in agriculture had positive impacts at endline but these had largely faded away four years later. Our results suggest that bundling nutrition and agriculture training may contribute to resilience as well as to sustained impacts on consumption, women’s empowerment, and asset holdings in the medium term. These have implications for the design of future gender- and nutrition-sensitive agricultural programs.